2011
DOI: 10.1371/journal.pone.0023441
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Very Premature Infants: A Systematic Review of Prediction Models

Abstract: ContextBeing born very preterm is associated with elevated risk for neonatal mortality. The aim of this review is to give an overview of prediction models for mortality in very premature infants, assess their quality, identify important predictor variables, and provide recommendations for development of future models.MethodsStudies were included which reported the predictive performance of a model for mortality in a very preterm or very low birth weight population, and classified as development, validation, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
92
0
11

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 49 publications
3
92
0
11
Order By: Relevance
“…Medlock et al (7) found that multivariate models of early clinical information predicted mortality in preterm infants better than BW or GA alone. Studies implementing the commonly used SNAP-II and SNAPPE-II scores showed a range of AUC values for the prediction of neonatal mortality, from 0.66 to 0.78 in SNAP-II studies and 0.60 to 0.91 in SNAPPE-II studies (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medlock et al (7) found that multivariate models of early clinical information predicted mortality in preterm infants better than BW or GA alone. Studies implementing the commonly used SNAP-II and SNAPPE-II scores showed a range of AUC values for the prediction of neonatal mortality, from 0.66 to 0.78 in SNAP-II studies and 0.60 to 0.91 in SNAPPE-II studies (8).…”
Section: Discussionmentioning
confidence: 99%
“…Early clinical information, including Apgar scores, gender, birth weight (BW), gestational age (GA) (4)(5)(6)(7), and illness severity scores, such as SNAP-II and SNAPPE-II have been used to predict short-term outcome (8). Quantitative analysis of multiple risk factors combined in a multivariate model can improve outcome prediction (7).…”
mentioning
confidence: 99%
“…Moreover, the predictive ability of our multipleoutcome model is comparable to recent models developed to predict mortality or survival free of severe morbidity. 8,15,19,34 Because the goal was to predict outcomes after initiation of intensive care, we excluded infants declared moribund or admitted for palliative care. The severity of each morbidity was ranked based on existing classification systems, [21][22][23] and the most common and debilitating morbidities, with proven cumulative and additive effects on long-term outcomes in neonates, 3,35 were classified as severe.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, prediction models examining a combined outcome of mortality and morbidities did not have better performance than models predicting mortality alone. [16][17][18][19] Therefore, for improved prediction it is important to distinguish between mortality and morbidities and to develop multivariable prediction models that reflect a range of outcomes along the severity spectrum.…”
mentioning
confidence: 94%
See 1 more Smart Citation